CLEC-2 Prevents Accumulation and Retention of Inflammatory Macrophages During Murine Peritonitis - Bourne, Joshua H.; Beristain-Covarrubias, Nonantzin; Zuidscherwoude, Malou; Campos, Joana; Di, Ying; Garlick, Evelyn; Colicchia, Martina; Terry, Lauren V.; Thomas, Steven G.; Brill, Alexander; Bayry, Jagadeesh; Watson, Steve P.; et al. (Frontiers in Immunology, 2021)
Platelets play a key role in the development, progression and resolution of the inflammatory response during sterile inflammation and infection, although the mechanism is not well understood. Here we show that platelet CLEC-2 reduces tissue inflammation by regulating inflammatory macrophage activation and trafficking from the inflamed tissues. The immune regulatory function of CLEC-2 depends on the expression of its ligand, podoplanin, upregulated on inflammatory macrophages and is independent of platelet activation and secretion. Mechanistically, platelet CLEC-2 and also recombinant CLEC-2-Fc accelerates actin rearrangement and macrophage migration by increasing the expression of podoplanin and CD44, and their interaction with the ERM proteins. During ongoing inflammation, induced by lipopolysaccharide, treatment with rCLEC-2-Fc induces the rapid emigration of peritoneal inflammatory macrophages to mesenteric lymph nodes, thus reducing the accumulation of inflammatory macrophages in the inflamed peritoneum. This is associated with a significant decrease in pro-inflammatory cytokine, TNF-α and an increase in levels of immunosuppressive, IL-10 in the peritoneum. Increased podoplanin expression and actin remodelling favour macrophage migration towards CCL21, a soluble ligand for podoplanin and chemoattractant secreted by lymph node lymphatic endothelial cells. Macrophage efflux to draining lymph nodes induces T cell priming. In conclusion, we show that platelet CLEC-2 reduces the inflammatory phenotype of macrophages and their accumulation, leading to diminished tissue inflammation. These immunomodulatory functions of CLEC-2 a novel strategy to reduce tissue inflammation and could be therapeutically exploited through rCLEC-2-Fc, to limit the progression to chronic inflammation.